Pembuatan, pengkalibrasian dan pengujian model fisis alat sistem elektromagnetik ternormalisasi geometerik=Development, calibration and physical modeling examination of a geometry ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
It has been already made, calibrated and tested by physical model an instrument of geometry normalized electromagnetic system. This instrument is better than the previous instrument (horizontal loop electromagnetic system) since it is relatively not sensitive to geometrical factor (geometry normalized), i.e., the distance, height differences, and angle between transmitter and receiver coils. Beside that this instrument has no interconnecting cable between transmitter and receiver, optimum noise reduction, and electronical distance measurement system. Simultaneously transmission of two electromagnetic waves with different frequencies will induced an eddy current in surrounding conductor or ore body. This current will produce secondary electromagnetic fields which are measured by the receiver together with the primary fields. Measurement of percent change of vertical component of the field will give the anomaly caused by the conductor.